Sex dimorphism of cortical water diffusion in normal aging measured by magnetic resonance imaging - Ng, Shu-Hang; Hsu, Wen-Chiun; Wai, Yau-Yau; Lee, Jiann-Der; Chan, Hsiao-Lung; Chen, YaoLiang; Fung, Hon-Chung; Wu, YihRu; Tsai, Ming-Lun; Wang, Jiun-Jie (Frontiers in Aging Neuroscience, 2013)
Background The purpose of this study was to examine sex dimorphism in water diffusion in the brain throughout the normal aging process by magnetic resonance imaging. Methods Diffusion-weighted images covering the majority of the brain were acquired from 77 healthy participants. Both the mean water diffusivity and diffusion kurtosis were calculated from the cortical regions and parcellated according to the template in Anatomical Automatic Labeling. The mean water diffusivity and diffusion kurtosis from both sexes were examined and subsequently correlated with age. Statistical significance was set at a threshold of p